Sustainability indicators for the Portuguese cork industry - Perlin, Ana Paula (2013)
Sustainable development proves to be an important focus of attention from industries once to modern society the impact of humans on the environment in which it operates is becoming increasingly complex. There is a growing concern for the environment and for the scarcity of available natural resources that are frequently related to the negative consequences brought by the industrial manufacturing system. Therefore, a framework incorporating sustainability indicators is an useful tool for decision making, policy formulation and public communication of economic, environmental and social performance of each organization. The present study aims to conduct a detailed study about the cork industry in Portugal, presenting a proposal of a set of sustainability indicators. These indicators are already being used in the industries in general, and can represent a starting point for the development of indicators that measure sustainability for this sector.